Food and the growth of introduced milkfish, Chanos chanos (Forsskal, 1775) in Sermo Reservoir, Kulon Progo - Djumanto Djumanto; Bayu Eko Pranoto; Vinta Seta Diani; Eko Setyobudi (Jurnal Iktiologi Indonesia, 2017)
The purpose of the research was to study feeding preferences and the growth of milkfish introduction into Sermo reservoir Kulon Progo regency. Research was carried out by introduction of milkfish juvenile which body length was ranges of 5-7 cm and weight of 0.6-1.0 g at a number of 10,000 individual fish. Fish sampling using gill nets was conducted monthly from May to October 2015. The captured milkfish brought to the laboratory for some measurements i.e length and weight of an individual fish, intestine length, and gut content investigation. The surface water plankton sample collected by a plankton net, then preserved in formaldehyde, identified and counted the number each plankton species. Data were analyzed to determine relative gut length, food type and feeding preferences, growth rate and length weight relationships. The results showed that relative intestinal length was 5.4 to 6.4, so milkfish categorized as herbivores. Phytoplankton was the only food found in the intestine fish size <14 cm, while zooplankton was found in fish size >15 cm. Zooplankton proportion in digestive tract increased as well as the size of milkfish. The dominant species of phytoplankton found in the digestive tract was Nitzschia sp., whereas zooplankton was Cyclop sp. and Diaptomus sp. The juvenile milkfish growth well in Sermo reservoir. The growth rate of daily length was ranged from 0.0084 to 0.2056 cm, while the growth rate of daily weight ranged from 0.0630 to 1.1182 g. The length weight relationship of milkfish formed an equation W = 0.0069 L 3 0186 with the regression index R2 = 0.98, so the growth of milkfish showed an isometric growth pattern. Further research is needed to determine the impact of the introduction of milkfish to the fish communities in the Sermo reservoir area. Abstrak Tujuan penelitian adalah untuk mengkaji makanan dan pertumbuhan ikan bandeng tebaran di waduk Sermo Kabupaten Kulon Progo. Penelitian dilakukan dengan menebar yuwana ikan bandeng yang panjang tubuh berkisar 5-7 cm dan bo-bot 0,6-1,0 g ke perairan Waduk Sermo sebanyak 10.000 ekor. Sampling ikan bandeng menggunakan jaring insang dilakukan tiap bulan sekali dari Mei sampai Oktober 2015. Ikan bandeng yang terjerat jaring dibawa ke laboratorium untuk diukur panjang, ditimbang bobot individu, dan dilakukan pembedahan untuk diambil saluran pencernaannya. Sampling plankton dilakukan dengan mengambil air permukaan menggunakan ember dan menyaring dengan plankton net, kemudian diawetkan dalam larutan formalin hingga identifikasi dan penghitungan jenisnya. Data dianalisis untuk me-nentukan jenis makanan dan pemilihan makanan, laju pertumbuhan, panjang usus relatif, dan hubungan panjang bobot. Hasil penelitian menunjukkan panjang usus relatif ikan bandeng sebesar 5,4-6,4 yang dikategorikan sebagai ikan herbi-vora. Jenis makanan yang ditemukan pada ikan berukuran <14 cm hanya fitoplankton, sedangkan zooplankton ditemu-kan pada ikan yang berukuran >15 cm. Proporsi zooplankton pada usus ikan semakin banyak seiring ukuran ikan bandeng. Jenis fitoplankton yang ditemukan dominan pada saluran pencernaan adalah Nitzschia sp., sedangkan zooplankton adalah Cyclop sp. dan Diaptomus sp. Yuwana ikan bandeng dapat tumbuh baik di kawasan Waduk Sermo. Laju pertumbuhan panjang harian berkisar 0,0084 - 0,2056 cm, sedangkan laju pertumbuhan bobot harian berkisar 0,06301,1182 g. Hubungan panjang bobot ikan bandeng membentuk persamaan W=0,0069 L 3,0186 dengan indeks regresi R2=0,98, sehingga ikan bandeng cenderung memiliki pola pertumbuhan isometrik. Penelitian lebih lanjut diperlukan untuk mengetahui dampak introduksi ikan bandeng pada komunitas ikan di Waduk Sermo.